Height is associated with incident atrial fibrillation in a large Asian cohort. (1st April 2020) - Park, Young Min; Moon, Jeonggeun; Hwang, In Cheol; Lim, Hyunsun; Cho, Bokeum
Abstract: Background: Although increased height is associated with a risk of atrial fibrillation (AF), the mechanism is not well understood. We aimed to explore whether this association varies with metabolic conditions. Methods and results: We used the database from the 14-year Korea National Health Insurance Service–National Sample Cohort. The data of 368, 206 adults older than 20 years who received a health check-up were analyzed to explore the association of height and AF risk. Cox proportional hazards regression models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) for associations of height with the risk of AF. During the median follow up duration of 8.46 years, 2641 (0.72%) patients were diagnosed with AF at 3, 070, 724 person-years. Overall, greater height was significantly associated with AF risk (HR per 5 cm, 1.22; 95% CI, 1.03–1.05). The association did not vary with age, sex, obesity, hypertension, and diabetes. Conclusion: Metabolic conditions do not affect the higher risk of AF in tall people. Highlights: It is unclear whether metabolic conditions affect higher AF risk in tall people. This large Asian cohort study confirmed the association between stature and AF risk. High AF risk in tall people was not influenced by metabolic conditions.